The Relationship Between Childhood Emotional Abuse and Symptoms of Depression: Behavioral Disorders Mediating Effects - Sari, Meita; Sunawan, Sunawan; Awalya, Awalya (Universitas Negeri Semarang, 2023)
Adolescence is the most prime phase of life in, so teenagers or adolescents are expected to have good mental health to enable them express and develop. However, this phase is vulnerable to depression symptoms, particularly during the university selection. This study sought for examining the relationship between childhood emotional abuse and symptoms of depression mediated by behavioral disorders. It was an ex post facto study and involved 270 freshmen. Their data were collected using Center for Epidemiologic Studies Depression Scale (CES-D), adolescents behavioral problem scale (SMP-R), and Emotional Abuse Questionnaire (EAQ) that have passed the validity and reliability tests. Following the data collection, the obtained data were analyzed using Andre F. Hayes’ model 4. Findings revealed that the childhood emotional abuse was significantly related to behavioral disorders (β=0.478, p<0.01) and symptoms of depression (β=0.586, p<0.01). In addition, there found a significant relationship between behavioral disorders and depressive symptoms (β=0.122, p<0.01). In addition, there is an indirect effect value of β=0.058 se=0.023. The implications for guidance and counseling practice will be discussed.